Local Election of Nepal 2017: An Overview of Gender Inclusion Prospective - Sijapati, Dipendra Bikram (Journal of Population and Development, 2020)
Gender refers to the socially constituted relations between men and women. It focuses on power relations, roles and challenges along with the existing women's subordination in the society. Gender Inclusiveness is additional diverse activity and process of local governments, local institutions like Ward, Rural Municipality, District Coordination Committee and Municipality with self-reliant local governance and sustainable and effective service providing agencies. This article based on the objective to highlight the existing variation of women's inclusion in local governments among developed and developing countries. It analyses the provisions regarding inclusion addressed in the federal Constitution of Nepal in local elections. This paper widely covers concept, definition, theories, practice, situation, laws, policies and program at all levels. The paper is based on secondary sources of information, data published by Election Commission 2017, in Nepal. The raw data are analysed using the Excel spread program on computer and are calculated in frequency distribution and percentage to make its meaningful analysis. Data are carefully analysed and interpreted for generalization. The gender inclusion in local government is gradually increasing. As in national election 2017, the female elected members in local government are almost 40 percent in the districts of Nepal and the data is more than allocated (33%) by the Constitution of Nepal 2015 and election manifestos of different political parties. All the acts, policies and constitutions also emphasized the gender inclusion in all sector of Nepalese government.